Ba2+ unmasks K+ modulation of the Na+-K+ pump in the frog retinal pigment epithelium (The Rockefeller University Press, 1985)
This paper presents electrophysiological evidence that small changes in [K+]o modulate the activity of the Na+-K+ pump on the apical membrane of the frog retinal pigment epithelium (RPE). This membrane also has a large relative K+ conductance so that lowering [K+]o hyperpolarizes it and therefore increases the transepithelial potential (TEP). Ba2+, a K+ channel blocker, eliminated these normal K+-evoked responses; in their place, lowering [K+]o evoked an apical depolarization and TEP decrease that were blocked by apical ouabain or strophanthidin. These data indicate that Ba2+ blocked the major K+ conductance(s) of the RPE apical membrane and unmasked a slowing of the normally hyperpolarizing electrogenic Na+-K+ pump caused by lowering [K+]o. Evidence is also presented that [K+]o modulates the pump in the isolated RPE under physiological conditions (i.e., without Ba2+). In the intact retina, light decreases subretinal [K+]o and produces the vitreal-positive c- wave of the electroretinogram (ERG) that originates primarily in the RPE from a hyperpolarization of the apical membrane and TEP increase. When Ba2+ was present in the retinal perfusate, the apical membrane depolarized in response to light and the TEP decreased so that the ERG c-wave inverted. The retinal component of the c-wave, slow PIII, was abolished by Ba2+. The effects of Ba2+ were completely reversible. We conclude that Ba2+ unmasks a slowing of the RPE Na+-K+ pump by the light-evoked decrease in [K+]o. Such a response would reduce the amplitude of the normal ERG c-wave.